Role Of Public Prosecutors In Corruption Crime Prosecution - Agung Nugroho Santoso; Sri Kusriyah (Law Development Journal, 2021)
The aims of this study are as follows: To identify and analyze the role of the Public Prosecutor in prosecuting defendants for corruption. To find out and analyze the efforts that will be made by the Public Prosecutor if the decision handed down by the Judge of the Corruption Court is not in accordance with the demands of the Public Prosecutor. The approach method used in this study is a sociological juridical research method. The specifications in this study are analytical descriptive. Based on the results of this study, the role of the Public Prosecutor in Prosecuting Defendants of Criminal Acts of Corruption, namely the public prosecutor in carrying out prosecutions for criminal acts of corruption has been sufficient to prove the fulfillment of the elements of criminal acts of corruption that were violated by the defendant as a result of the actions committed. Starting from the investigation, prosecution, legal action which then if it already has permanent legal force, the prosecutor's office as in making charges against criminal acts of corruption is regulated in Article 137, Article 139 and Article 143 of the Criminal Procedure Code as well as Act No. 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia. Indonesia, thus giving confidence to the judge that the defendant's actions had violated the criminal provisions he was charged. Examination of the Cassation Level for Legal Interests (Article 259 of the Criminal Procedure Code). Review of Court Decisions that have Permanent Legal Force (Article 263 of the Criminal Procedure Code).